Between nature and culture: animals and humans in Old Norse literature - Bourns, T (2018)
This thesis demonstrates how animals and humans are interconnected in Old Norse literature. The two categories are both constructed and challenged in a variety of ways, depending on the textual genre and animal species. It thus reveals medieval Norse-Icelandic ideas, values, and beliefs about animals. The thesis is theoretical, comparative, and interdisciplinary, yet firmly rooted in a close reading of the sagas and analysis of their cultural-historical context. The first chapter explores relationships between people and domestic animals, namely horses and dogs, and to a lesser extent, cats and livestock. The second chapter evaluates the limitations to the human-animal relationship: prohibitions against bestiality and the consumption of certain animals as meat. The third chapter studies animals in dreams, which reflect human characters and share their fate and defining characteristics. The fourth chapter investigates human-animal transformations, whether physical, psychological, or both. The fifth chapter analyses human-animal communication, with a particular focus on human comprehension of the language of birds. The sixth chapter considers relations between animals and gods in Norse mythology; these parallel the connections between humans and animals in the sagas. The thesis determines how the human/animal dichotomy might have been thought about differently before and after the conversion to Christianity, with boundaries between animal and human becoming more clearly delineated; it examines how medieval Icelandic authors wrote about animals in experiential terms, but also drew upon conventional symbolism from continental Europe; and it proves how these literary representations of animals reflect an environmental ideology that was actively engaged with the imaginative, the supernatural, and the animal.